La capacitación docente en competencias digitales y su interconexión con el Marco de Competencias TIC UNESCO en la Universidad Nacional Loja - Jimbo Sarmiento, Dennis Jefferson (2024)
Training in digital teacher competencies (DTC) has become a central axis in education, especially at the university level. At the National University of Loja, the effective integration of these competencies is intertwined with the TIC UNESCO Competency Framework, which provides a solid and updated reference to improve the quality of education, preparing educators to meet the challenges and needs of higher education in the digital age. Among the objectives of the project, the level of teacher training in digital competencies was analyzed at the National University of Loja, and its interconnection with the degree of application of the TIC UNESCO Competency Framework for Teachers version 3, which determined the causes and effects within this phenomenon, through a quantitative study that allowed a comprehensive understanding of the results and identified the correlations between the variables. The methodological process used was a cross-sectional quantitative approach, in which a report of trainings executed by the institution on DTC development topics was analyzed, also the perception of university faculty was collected through the application of a 24-item questionnaire to 157 teachers, focused on determining the level of training in DTC and the degree of application of the TIC UNESCO DTC, allowed, from the analysis of the results, to confirm the importance of the implementation of continuous training programs in DTC. Between the years 2019 and 2023 the institution executed 5 trainings to the teaching staff on topics related to the development of the DTC, which stands as a representative strength. The average coefficient of the DTC training was 4.06, which classifies it in the High and Very High level. The average coefficient of the TIC UNESCO DTC application was 4.26, which segments it into High and Very High levels. The non-parametric tests indicate that the variables are dependent on each other with a significant and direct correlation at a medium level. It is concluded that the faculty of the National University of Loja is located in representative levels of training and application of the DTC, which is a valuable advantage for the institution, since it allows it to adapt to the environment, changes, and leads it to become a leader in the provision of quality higher education. Keywords: Teacher education; Teacher attitudes; Higher education; Educational technology; University curriculum.